Inadequate fruit and vegetable intake in people with psychosis. (November 2014) - Hahn, Lisa A; Galletly, Cherrie A; Foley, Debra L; Mackinnon, Andrew; Watts, Gerald F; Castle, David J; Waterreus, Anna; Morgan, Vera A
Objective: The objective of this study was to identify factors associated with poor dietary intake (less than four servings of fruit and vegetables daily) in a large nationally representative sample of adults with psychotic disorders. Methods: The sample comprised 1286 adults aged 18–64 years who took part in the second Australian national survey of psychosis. Dietary information was obtained using a standardised questionnaire; all participants provided fasting blood samples. Variables that may be related to diet and nutritional intake were investigated; these included demographics, physical health outcomes, physical activity, substance use, symptom severity and financial difficulty. Dietary status was explored by sex, age and body mass index using univariate analyses, while a multivariate analysis was performed to identify predictors of low nutritional intake. Results: Approximately 74% of participants ate less than four servings of fruit and vegetables daily. This was associated with a lower body mass index ( p <0.05), lower levels of physical activity ( p <0.05), sedentary behaviour ( p <0.05), substance use ( p <0.001), more negative symptoms ( p <0.05), eating less frequently ( p <0.001), consuming whole fat milk compared to low fat milk ( p <0.05), adding salt to food ( p <0.05) and financial difficulty ( p <0.05). Male sex and younger age (18–34 years) were also associated with lower fruit and vegetable intake ( p <0.001). A multivariate regression analysis showed that current smoking ( p <0.001) and alcohol ( p <0.01) and cannabis abuse ( p <0.05) were risk factors for lower fruit and vegetable intake. Conclusion: The findings suggest that poor diet in people with psychosis, as reflected by less than four servings of fruit and vegetables daily, is accompanied by other unhealthy behaviours, which has important implications for the development of effective interventions. Importantly, current smoking is a significant predictor of dietary inadequacy.